The political and institutional independence of U.S. monetary policy - M.A. AKHTAR; H. HOWE (PSL Quarterly Review, 2013)
The work deals with the institutional arrangements underlying the decision-making process for U.S. monetary policy. The primary focus of analysis is on the central bank’s political and institutional independence and accountability for monetary policy. Specifically, the authors review details of the institutional framework and recent Congressional attempts to change that framework. The overall aim is to provide perspective on the autonomy of U.S. monetary policy by considering, among other things, recent political challenges to the structure of the Federal Reserve.